Bone Mechanical Properties and Mineral Density in Response to Cessation of Jumping Exercise and Honey Supplementation in Young Female Rats - Sadat Tavafzadeh, Somayeh; Foong, Kiew Ooi; Chee, Keong Chen; Sulaiman, Siti Amrah; Leong, Kim Hung (Hindawi Publishing Corporation, 2015)
This study investigated effects of cessation of exercise and honey supplementation on bone properties in young female rats. Eightyfour 12-week-old Sprague-Dawley female rats were divided into 7 groups: 16S, 16J, 16H, 16JH, 8J8S, 8H8S, and 8JH8S (8 = 8 weeks, 16 = 16 weeks, S = sedentary without honey supplementation, H = honey supplementation, and J = jumping exercise). Jumping exercise consisted of 40 jumps/day for 5 days/week. Honey was given to the rats at a dosage of 1 g/kg body weight/rat/day via force feeding for 7 days/week. Jumping exercise and honey supplementation were terminated for 8 weeks in 8J8S, 8H8S, and 8JH8S groups. After 8 weeks of cessation of exercise and honey supplementation, tibial energy, proximal total bone density, midshaft cortical moment of inertia, and cortical area were significantly higher in 8JH8S as compared to 16S. Continuous sixteen weeks of combined jumping and honey resulted in significant greater tibial maximum force, energy, proximal total bone density, proximal trabecular bone density, midshaft cortical bone density, cortical area, and midshaft cortical moment of inertia in 16JH as compared to 16S. These findings showed that the beneficial effects of 8 weeks of combined exercise and honey supplementation still can be observed after 8 weeks of the cessation and exercise and supplementation.